Business model development, founders' social capital and the success of early stage internet start‐ups: a mixed‐method study. (26th May 2015) - Spiegel, Olav; Abbassi, Puja; Zylka, Matthäus Paul; Schlagwein, Daniel; Fischbach, Kai; Schoder, Detlef
Abstract: Information technology (IT) and entrepreneurship are more closely related than ever. The internet, in particular, inspires the current 'generation start‐up'. While some early stage internet start‐ups have quickly become major successes, others fail to secure required follow‐up funding and collapse. In this paper, we build on and extend the emerging business model research stream with the aim of better understanding the differences between successful and unsuccessful early stage internet start‐ups. In the qualitative first part of our mixed‐method study, 17 expert informant interviews reveal that internet start‐up business models are in permanent flux, continually changed and adapted by founders, who identify their professional social network (i.e. their social capital) as a critically important factor for developing the business model and ultimately making their start‐ups successful. In the quantitative second part of the study, we test this claim based on a social network analysis of 70 internet start‐ups and their 145 founders. We find strong support for the critical importance of the founders' social capital for early stage internet start‐up success. The findings of this study advance our understanding of the relationship between founders' social capital, the development of business models and the success of early stage internet start‐ups.